Eletromiografia dos músculos temporal e masseter em crianças com mordida cruzada posterior direita - Pissulin, Cristiane Neves Alessi; Bérzin, Fausto; de Faria Negrão Júnior, Rúben [UNESP]; Oliveira, Acary Souza Bulle; Pissulin, Flávio Danilo Mungo (Universidade Estadual de Maringa, 2010)
This study proposal was to evaluate the changes at a masticatory muscle temporalis and masseter, through a eletromyographic, at ponters of the right unilateral bite posterior, verifying the difference at the eletric activity between right and left sides. Twenty female volunteers, with ages between 7 and 8 (x = 7.4). The eletromyographics signals were collected in both sides in all volunteers in rest situations and in an usual isotonic mastication, right, left and bilateral and the maximun isometric constriction, which sinal was used to the eletric activity amplitude normalization. The results signed that the right masseter muscle presents an expressive statistic difference, if compared with the left masseter muscle during the left and right mastication, suggesting a right unilateral mastication. The muscle haven't gotten any expressive variance in this amplitude which remained to a proximate flat noticed in a right and habitual mastication, suggesting a right and one sided mastication during the left mastication occurs a raise of the eletric signal amplitude of the muscle left masseter. The right masseter muscle haven't gained any expressive variance, which remained in a proximate flat observed in an usual and right mastication, suggesting a muscular pattern hyperfunction next to the dental crossing.
Electromyography of the temporalis and masseter muscles in children with right unilateral crossbite
Keywords: Electromyography; Malocclusion; Mastication; amplitude modulation; child; controlled study; crossbite; electric activity; electromyography; female; human; human experiment; human tissue; masseter muscle; mastication; masticatory muscle; muscle isometric contraction; muscle isotonic contraction; normal human; school child; signal transduction; temporalis muscle; volunteer